Horta escolar como espaço didático para a educação em ciências - Brandão, Gustavo Krysnamurthy Linhares (2012)
This work has as focus to analizes vegetables gardens in school like some tool to learn in the public school, having as bases interdisciplinarity, in context, in dialog, in motivation and in the problematization. The subject of investigation of this search is organically linked to the social and cultural actual configurations in contemporany Brazil marked by transformations come from the seek of a better public education. It shows as key point of analisys from investigative fenomenum, the historic context of efervecency of politics that overcomes the bank education critisized by Paulo Freire, strongly marked by a confluency between the participative project and the project of estructural adjust. It has the propose of share with institutions school, some reflexions and conclusions about mechanisms of implementation of the school vegetables gardens while place to learn, in public schools, as well as identify the overcomes, limities, possibilities from this purpose that was helped by the efective participation of representants from envolved people. Segments, parents, students, teachers, employees and núcleus manager from school, promoting the development of a participation pedagogy using innovative practical in relations intra-school and, from this with community. The methodologic procedure compreenhended bibliographic studies, documments and searches of fields in qualitative nature in the meaning of knowledge of social experience from several subjecties into the garden vegetables implementation in public school. The result of empiric investigation realized in two garden vegetables schools in public schools in Fortaleza city shows that the learning leaded by the interdisciplinarity, by motivation, by contextualization, by problematization and by dialog can be made with the participation of everybody and dedication. The school vegetables gardens by their turn, are hibrid dynamic places, promoting the significative knowledge and capable of overcome the logic of bank education , forming critics citizen and reflexives, into a freiriano context. From experiences lived in didatic space of the vegetable garden, we organized a blog, the learning product o four research, we show lived situations by teachers, students, coordenators, monitors and by manager of Y school . This tool will improve us to lead the process of implementation of vegetable gardens in another learning institutions.